Muhammadiyah Dan Ideologi Islam Berkemajuan - Agustang, Andi Dody May Putra; Agustang, Andi; Jumadi, Jumadi (Phinisi Integration Review, 2022)
This study aims to determine the suitability of the perception of the Muhammadiyah community in the city of Makassar to the ideology of Progressive Islam. The subject of this study is the Muhammadiyah community in the city of Makassar. These include: (1) being involved or having been involved in the structure (management) of Muhammadiyah Makassar, (2) Ordinary citizens, namely those who have never been involved in the structure (management) of Muhammadiyah. This research selects informants purposively. By using descriptive qualitative analysis. The result showed that the internalization of progressive Islam by Muhammadiyah members was not uniform, but it gave rise to many perceptions. There are at least two categories of typology that the researchers found in relation to the concept of progressive Islam and the perception of the Muhammadiyah community in Makassar. The first is a "perceptual typology" while the second is a "misperception typology". The first typology is the compatibility between the concept of Muhammadiyah's Progressive Islam and the understanding of the citizens. the second typology shows the perception of Muhammadiyah residents that does not match the concept of Progressive Islam with the perception of Muhammadiyah Makassar residents. The formation of various typologies of knowledge, which on the one hand is in accordance with the concept of Progressive Islam, on the other hand, it is not in accordance with the concept of Progressive Islam, due to aspects of material conditions that they do not accept singly. The socio-cultural conditions of Muhammadiyah members are not only involved in the Muhammadiyah organ alone. Thus, it allows cross-knowledge. The mutual influence between knowledge in Muhammadiyah and outside Muhammadiyah is very possible. And this has been proven to happen to Muhammadiyah members in internalizing Progressive Islam.Â Muhammadiyah, progressive Islamic ideology